Lithium-ion solid electrolyte, lithium-ion ternary positive electrode material and preparation methods of lithium-ion solid electrolyte and lithium-ion ternary positive electrode material

By combining the method of combining the soluble gel method and the common precipitation method, the nano -level lithium -ion solid electrolyte is prepared, solving the problem of more miscellaneous materials and low nanlatinization in the existing technology, improved the conductivity and cycle performance, and enhanced the enhancement The capacity and stability of the ternary orthopedic material.

CN119381526AActive Publication Date: 2025-01-28HEFEI GUOXUAN HIGH TECH POWER ENERGY CO LTD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411484398.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing preparation methods for lithium-ion solid electrolytes have problems such as many heterogeneous phases, low nanoification degree and low conductivity of preparation materials, and it is difficult to effectively improve the circulation performance and capacity of the ternary positive electrode material.

Method used

The method of combining the soluble gel method and the common precipitation method is used to prepare lithium ions solid electrolytes, configure the colloid through the water system thickener, and perform co -precipitation in the liquid phase, control the ionic response rate and nuclear growth rate, and obtain the nano -level LATP sediment. Essence

Benefits of technology

The nano -level LATP solid electrolyte is achieved efficiently, improved the conductivity and circulation performance of the material, and enhanced the capacity and stability of the ternary positive pole material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381526A_ABST
    Figure CN119381526A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion solid electrolyte and a preparation method thereof. The preparation method comprises the following steps: dissolving an aqueous thickener in pure water to obtain a colloid, and dividing the colloid into two parts; adding a lithium salt, an aluminum salt and a titanium salt into the part of colloid, and adding an organic chelating agent in a water bath; adding a phosphate solution formed by neutralizing an alkaline substance A and purified phosphoric acid into the other part of colloid; mixing the two parts, and adding an alkaline substance B to react while stirring in a water bath to obtain a mixed glue solution; raising the temperature and increasing the stirring speed to obtain turbid liquid; and filtering the turbid liquid, washing and drying to obtain an LATP precursor, and calcining and ball-milling the LATP precursor to obtain the LATP powder material. The method comprises the following steps: preparing a colloid by using a water-based thickening agent, dissolving soluble salts by using the colloid, obtaining a precipitate in a colloid liquid phase by using a coprecipitation method, and drying and calcining the precipitate to finally obtain LATP, so that the method has the advantages of a sol-gel method and the coprecipitation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a lithium ion solid electrolyte and a lithium ion ternary positive electrode material and a preparation method thereof. Background Art

[0002] Lithium Aluminum Titanium Phosphate (Li 1+x Al x Ti 2-x (PO4)3, LATP) is a lithium-ion solid electrolyte material with high ionic conductivity (~10 -3 S / cm), excellent chemical and thermodynamic stability, good cathode adaptability and wide electrochemical window, etc. At the same time, it has attracted widespread attention due to its extremely low raw material cost and preparation cost, and is considered to be one of the solid electrolytes with the most development potential.

[0003] LATP can be used as a coating agent to coat the particle surface of lithium-ion high-nickel ternary positive electrode material (NCM, N, C, and M in NCM refer to Ni, Co, and Mn respectively, and the ternary positive electrode material in which the Ni element accounts for more than 80% of the three elements of Ni, Co, and Mn is called ternary high-nickel material). After high-temperature treatment, a LATP-NCM interface layer can be formed. This interface layer can effectively resist the erosion and damage of the electrolyte during the charging and discharging process of the ternary material, while increasing the insertion and deinsertion rate of lithium ions, thereby improving the cycle performance of the ternary positive electrode material and improving the capacity of the material.

[0004] At present, the synthesis methods of LATP solid electrolytes mainly include the following:

[0005] (1) High-temperature solid-phase method. As a typical solid-phase synthesis method for synthesizing inorganic solid electrolytes, this method usually involves crushing, activating and homogenizing the required raw materials through ball milling or other mechanical grinding methods, and then calcining them at high temperature to obtain LATP solid electrolytes. This method has the advantages of simple process and high yield, but it also has the disadvantages of having many impurities in the prepared materials, low degree of nano-crystallization and low conductivity.

[0006] (2) Sol-gel method. The sol-gel method uniformly mixes these raw materials in the liquid phase and performs hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. Subsequently, the sol is aged, and the particles slowly polymerize to form a gel with a three-dimensional spatial network structure that loses fluidity. The gel network is filled with solvents that have lost fluidity to form a gel. Finally, the gel is dried, sintered and solidified to prepare molecular and even nano-substructured materials. The microstructure of LATP can be accurately reconstructed from the atomic / molecular size. Compared with the high-temperature solid-phase method, a highly nano-sized LATP solid electrolyte can be synthesized at a lower sintering temperature. Although the solid-phase synthesis method can prepare materials on a large scale, the prepared LATP solid electrolyte is usually accompanied by defects and impurities, which greatly reduces its electrochemical performance.

[0007] (3) Co-precipitation method. In addition to the sol-gel method, the co-precipitation method is also often used to precisely control the composition and morphology of the prepared materials. The salts of the required elements are dissolved in pure water to form a solution, and then alkali solution is added to the solution to induce precipitation. The morphology and composition of the precipitate are controlled by controlling the parameters in the reaction process such as pH, stirring rate and temperature. The precipitate is filtered and then calcined at high temperature. Compared with the sol-gel method, the co-precipitation method has the advantages of wider raw material selection, large synthesis yield and simple process control. However, compared with the sol-gel method, the particle nucleation and growth in the co-precipitation process have the disadvantage that the nucleation and growth rate is too fast to be controlled. Therefore, the co-precipitation method usually prepares nano- and micron-sized particle materials. Summary of the invention

[0008] Based on this, the purpose of the present invention is to provide a lithium ion solid electrolyte and a lithium ion ternary positive electrode material and a preparation method thereof to solve the above problems.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] The present invention first provides a method for preparing a lithium ion solid electrolyte, which comprises the following steps:

[0011] S1. dissolving the aqueous thickener in pure water to obtain a colloid, dividing the colloid into two parts and recording them as colloid A1 and colloid A2 respectively;

[0012] S2. Adding lithium salt, aluminum salt and titanium salt to the colloid A1, and adding an organic chelating agent in a water bath;

[0013] S3. neutralizing the alkaline substance A with purified phosphoric acid to form a phosphate solution and adding the phosphate solution to the colloid A2;

[0014] S4. The colloid A1 and the colloid A2 are mixed, and an alkaline substance B is added under stirring in a water bath to adjust the pH to obtain a mixed colloid solution; then the temperature is increased and the stirring speed is increased to obtain a suspension;

[0015] S5. Filter the suspension, wash and dry to obtain a LATP precursor, calcine and ball-mill the LATP precursor to obtain a LATP powder material.

[0016] The present invention first uses an aqueous thickener to configure a colloid and uses the colloid to dissolve soluble salts, then uses a coprecipitation method to obtain a precipitate in the colloidal liquid phase, and the precipitate is dried and calcined to finally obtain LATP, which has the advantages of both the sol-gel method and the coprecipitation method. The present invention combines the advantages of the sol-gel method and the coprecipitation method to prepare LATP, uses an aqueous thickener to configure a colloid, the colloid has a certain viscosity but can also dissolve soluble salts, but unlike conventional aqueous solutions, the ions dissolved therein cannot migrate quickly, so the use of the colloid for liquid phase reaction can play a role in controlling the ion reaction rate, so as to control the nucleation rate and the growth rate, thereby obtaining a nano-scale precipitate; the colloid loses its colloidal properties under high-speed stirring and heating, and can be similar to an aqueous solution and can be filtered to extract solids therein.

[0017] As a further improvement of the above scheme of the present invention, in step S1, the aqueous thickener is one of hydroxypropyl methylcellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, carboxymethyl cellulose, and sodium carboxymethyl cellulose;

[0018] And / or, in the colloid, the mass percentage of the water-based thickener is 1%-2.5%, and the viscosity of the colloid is 2000-3000 mPa·s.

[0019] As a further improvement of the above scheme of the present invention, in step S2, the lithium salt is lithium nitrate or lithium chloride;

[0020] And / or, in step S2, the aluminum salt is aluminum nitrate;

[0021] And / or, in step S2, the titanium salt is one of potassium titanium oxalate, titanium oxalate, and titanyl sulfate;

[0022] And / or, in step S2, the organic chelating agent is citric acid or oxalic acid;

[0023] And / or, in step S2, the temperature of the water bath is 1-10°C;

[0024] And / or, in step S2, according to the chemical formula of LATP Li 1+x Al x Ti 2-x(PO4)3 calculate the added amounts of the lithium salt, aluminum salt and titanium salt, wherein the concentration of the Al element is 0.065-0.36 mol / l, 1.3≤x≤1.8;

[0025] And / or, in step S2, the amount of the organic chelating agent is 0.5-2 times the total amount of the titanium aluminum metal ion substances.

[0026] As a further improvement of the above scheme of the present invention, in step S3, the alkaline substance A is ammonia water, sodium hydroxide or potassium hydroxide;

[0027] And / or, in step S3, according to the chemical formula of LATP Li 1+x Al x Ti 2-x (PO4)3 calculates the amount of the phosphate solution added, and the concentration of the phosphate solution is 0.15-0.6 mol / l.

[0028] As a further improvement of the above solution of the present invention, in step S4, the temperature of the water bath is 1-10°C;

[0029] And / or, in step S4, the alkaline substance B is ammonia water, sodium hydroxide or potassium hydroxide;

[0030] And / or, in step S4, the molar concentration of the alkaline substance B is 0.01-1 mol / l, and the pH of the mixed glue is 6-10;

[0031] And / or, in step S4, the stirring speed in the water bath is lower than 60 rpm / min, and the reaction time is 2-8 h;

[0032] And / or, in step S4, the heating is to raise the temperature of the mixed glue solution to 70-90° C., and the increasing the stirring speed is to increase the stirring speed to not less than 200 rpm / min;

[0033] And / or, in step S4, the viscosity of the suspension is less than 500 mPa·s.

[0034] As a further improvement of the above solution of the present invention, in step S5, the drying temperature is 110-180°C;

[0035] And / or, in step S5, the calcination temperature is 700-1100°C.

[0036] The present invention also provides a lithium ion solid electrolyte, which is prepared by the preparation method of the lithium ion solid electrolyte as described above.

[0037] The present invention also provides a method for preparing a lithium ion ternary positive electrode material, which comprises the following steps: mixing the lithium ion solid electrolyte as described above with the ternary high nickel material, and calcining to obtain a LATP-coated lithium ion ternary positive electrode material.

[0038] As a further improvement of the above solution of the present invention, the mass ratio of the LATP powder material to the ternary high-nickel material is 0.2-1.5%;

[0039] And / or, in the ternary high-nickel material, the Ni content among Ni, Co and Mn accounts for more than 80%;

[0040] And / or, the calcination temperature is 550-650°C.

[0041] The present invention also provides a lithium ion ternary positive electrode material, which is prepared by the preparation method of the lithium ion ternary positive electrode material as described above.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention combines the advantages of both the sol-gel method and the coprecipitation method to prepare LATP. First, a water-based thickener is used to configure a colloid. The colloid has a certain viscosity and can dissolve soluble salts, but unlike conventional aqueous solutions, the ions dissolved therein cannot migrate quickly. Therefore, the use of this colloid for liquid phase reaction can control the ion reaction rate to control the nucleation rate and growth rate, thereby obtaining a nanoscale precipitate. The colloid loses its colloidal properties under high-speed stirring and heating conditions, and can be similar to an aqueous solution. The solid can be extracted through a filtration device; then the coprecipitation method is used to obtain a precipitate in the liquid phase, and finally LATP is obtained. The present invention first uses an aqueous thickener to configure a colloid and uses the colloid to dissolve soluble salts, and then uses the coprecipitation method to obtain a precipitate in the colloidal liquid phase. The precipitate is dried and calcined to finally obtain LATP, which has the advantages of both the sol-gel method and the coprecipitation method.

[0044] The present invention can control the reaction nucleation and growth process like the sol-gel method, but avoids the processing and manufacturing difficulties brought by the formation of solids by the sol-gel method. It can also obtain precipitates in the liquid phase like the co-precipitation method, but avoids the difficulty of controlling the rate of the reaction nucleation and growth process in the liquid phase method. The required materials can be prepared in large quantities in a precipitation, washing and drying manner similar to the liquid phase method, and has the advantages of both methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a SEM image of the LATP powder material prepared in Example 1;

[0046] Figure 2This is the SEM image of the LATP-coated lithium-ion ternary positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0047] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0049] Example 1

[0050] This embodiment provides a lithium ion ternary positive electrode material, and the preparation method thereof includes the following steps:

[0051] S1. Dissolve hydroxymethyl cellulose in pure water to form an aqueous colloid with a viscosity of 2000 mPa·s, wherein the mass percentage of hydroxymethyl cellulose in the aqueous colloid is 1.5%; divide the aqueous colloid into two parts and record them as colloid A1 and colloid A2 respectively.

[0052] S2. Add lithium nitrate, aluminum nitrate, and titanium oxalate to colloid A1, and the amount of lithium nitrate, aluminum nitrate, and titanium oxalate added satisfies the chemical formula of LATP: Li 2.8 Al 1.8 Ti 0.2 The ratio of each element in (PO4)3 is that the concentration of Al element is 0.144 mol / l, the solution temperature is controlled at 5-6°C by a water bath, and citric acid is added as an organic chelating agent. The amount of citric acid is 1 times the total amount of aluminum nitrate and titanium oxalate.

[0053] S3. Neutralize ammonia water and purified phosphoric acid to form diammonium phosphate salt solution and add the diammonium phosphate salt solution to colloid A2. The amount of diammonium phosphate salt solution added satisfies the chemical formula of LATP: Li 2.8 Al 1.8 Ti 0.2 The ratio of each element in (PO4)3, the molar concentration of diammonium phosphate salt is 0.24 mol / l.

[0054] S4. Colloid A2 is slowly added to colloid A1, and the mixture is stirred at a low speed of 30 rpm / min. While stirring, 1 mol / l ammonia water is added to adjust the pH of the colloid to 7-8, so that the metal ions in colloid A1 and the phosphate groups in colloid A2 are precipitated. The reaction temperature is controlled at 5-6°C in a water bath. After stirring the mixture at a low speed for 6 hours, the reaction solution is heated to 80°C and the stirring speed is increased to 200 rpm / min. The high-speed stirring makes the thickener ineffective, and a suspension with a viscosity of less than 500 mPa·s is obtained.

[0055] S5. The suspension is filtered and the obtained solid is further washed with pure water. After washing, it is heated at 110° C. and vacuum dried to obtain a LATP precursor.

[0056] S6. The obtained LATP precursor is calcined at 800°C and ball-milled to obtain the LATP powder material Li 2.8 Al 1.8 Ti 0.2 (PO4)3.

[0057] S7. The obtained LATP powder material and the ternary high-nickel material (the molar ratio of Ni, Co, and Mn in NCM is 88:7:5) are mixed at a mass ratio of 1.5:98.5 using a high-speed mixer, and calcined at 600°C to obtain a LATP-coated lithium-ion ternary positive electrode material.

[0058] Figure 1 This is the SEM image of the LATP powder material prepared in step S6 of this embodiment. Figure 1 It can be seen that the LATP powder material prepared in this example presents highly nanosized spherical particles with a particle diameter of 100-200 nm. The spherical particles contain some fine particles that are broken due to ball milling.

[0059] Figure 2 This is a SEM image of the LATP-coated lithium-ion ternary positive electrode material prepared in step S7 of this embodiment. Figure 2 It can be seen that after the LATP prepared in this embodiment is further coated on the high-nickel ternary material as a coating material, a denser dark area can be seen on the micron-sized particles of the ternary material on the SEM. This is the two-phase interface area formed on the surface of the micron-sized particles of the ternary material after the nano-scale LATP and the ternary material are calcined and fused. Since this two-phase interface area is different from the properties of the pure ternary material, it presents different contrast in the SEM.

[0060] Example 2

[0061] This embodiment provides a lithium ion ternary positive electrode material, and the preparation method thereof includes the following steps:

[0062] S1. Dissolve hydroxymethyl cellulose in pure water to form an aqueous colloid with a viscosity of 2500 mPa·s, wherein the mass percentage of hydroxymethyl cellulose in the aqueous colloid is 2%; divide the aqueous colloid into two parts and record them as colloid A1 and colloid A2 respectively.

[0063] S2. Add lithium chloride, aluminum nitrate, and titanyl sulfate to colloid A1, and the amount of lithium chloride, aluminum nitrate, and titanyl sulfate added satisfies the chemical formula of LATP: Li 2.5 Al 1.5 Ti 0.5 (PO4)3, wherein the molar concentration of Al element is 0.15 mol / l, the solution temperature is controlled at 3-4°C by a water bath, and oxalic acid is added as an organic chelating agent, and the molar concentration of oxalic acid is 1 times the total molar concentration of aluminum nitrate and titanyl sulfate.

[0064] S3. Sodium hydroxide and purified phosphoric acid are neutralized to form a sodium dihydrogen phosphate salt solution, and the sodium dihydrogen phosphate salt solution is added to colloid A2. The amount of ammonium dihydrogen phosphate salt solution added satisfies the chemical formula of LATP Li 2.5 Al 1.5 Ti 0.5 (PO4)3, the molar concentration of sodium dihydrogen phosphate solution is 0.3 mol / l.

[0065] S4. Colloid A2 is slowly added to colloid A1, and the mixture is stirred at a low speed of 20 rpm / min. While stirring, 0.1 mol / l sodium hydroxide is added to adjust the pH of the colloid to 8-9, so that the metal ions in A1 and the phosphate groups in colloid A2 are precipitated. The reaction temperature is controlled at 3-4°C in a water bath. After stirring and reacting at a low speed for 4 hours, the reaction solution is heated to 90°C and the stirring speed is increased to 300 rpm / min. The high-speed stirring makes the thickener ineffective, and a suspension with a viscosity of less than 500 mPa·s is obtained.

[0066] S5. The suspension is filtered and the obtained solid is further washed with pure water. After washing, the solid is heated and dried in a vacuum at 150° C. to obtain a LATP precursor.

[0067] S6. The obtained LATP precursor is calcined at 900°C and ball-milled to obtain the LATP powder material Li 2.5 Al 1.5 Ti 0.5 (PO4)3.

[0068] S7. The obtained LATP powder material and the ternary high-nickel material (the molar ratio of Ni, Co, and Mn in NCM is 88:7:5) are mixed at a mass ratio of 1:99 using a high-speed mixer, and calcined at 620°C to obtain a LATP-coated lithium-ion ternary positive electrode material.

[0069] Example 3

[0070] This embodiment provides a lithium ion ternary positive electrode material, and the preparation method thereof includes the following steps:

[0071] S1. Dissolve hydroxymethyl cellulose in pure water to form an aqueous colloid with a viscosity of 3000 mPa·s, wherein the mass percentage of hydroxymethyl cellulose in the aqueous colloid is 2.5%; divide the aqueous colloid into two parts and record them as colloid A1 and colloid A2 respectively.

[0072] S2. Add lithium sulfate, aluminum chloride, and potassium titanium oxalate to colloid A1, and the amount of lithium sulfate, aluminum chloride, and potassium titanium oxalate added satisfies the chemical formula of LATP: Li 2.3 Al 1.3 Ti 0.7 (PO4)3 ratio, wherein the molar concentration of Al element is 0.156 mol / l, the solution temperature is controlled at 1-2°C by a water bath, and citric acid and oxalic acid (1:1) are added as organic chelating agents, and the molar concentration of citric acid is 1 times the total molar concentration of aluminum chloride and potassium titanium oxalate.

[0073] S3. The potassium dihydrogen phosphate solution formed by neutralizing sodium hydroxide and purified phosphoric acid is added to the colloid A2. The amount of ammonium dihydrogen phosphate solution added satisfies the chemical formula of LATP: Li 2.3 Al 1.3 Ti 0.7 (PO4)3, the molar concentration of potassium dihydrogen phosphate salt solution is 0.36 mol / l.

[0074] S4. Colloid A2 is slowly added to colloid A1, and the mixture is stirred at a low speed of 40 rpm / min. While stirring, 0.1 mol / l potassium hydroxide solution is added to adjust the pH of the colloid to 9-10, so that the metal ions in A1 and the phosphate groups in colloid A2 are precipitated. The reaction temperature is controlled at 1-2°C in a water bath. After stirring and reacting at a low speed for 2 hours, the reaction solution is heated to 95°C and the stirring speed is increased to 600 rpm / min. The high-speed stirring makes the thickener ineffective, and a suspension with a viscosity of less than 500 mPa·s is obtained.

[0075] S5. The suspension is filtered and the obtained solid is further washed with pure water. After washing, it is heated at 160° C. and vacuum dried to obtain a LATP precursor.

[0076] S6. The obtained LATP precursor is calcined at 1000°C and ball-milled to obtain the LATP powder material Li 2.3 Al 1.3 Ti 0.7 (PO4)3.

[0077] S7. The obtained LATP powder material and the ternary high-nickel material (the molar ratio of Ni, Co, and Mn in NCM is 88:7:5) are mixed at a mass ratio of 0.5:99.5 using a high-speed mixer, and calcined at 650°C to obtain a LATP-coated lithium-ion ternary positive electrode material.

[0078] Comparative Example

[0079] The lithium-ion ternary positive electrode material of this comparative example adopts an uncoated ternary high-nickel material (the molar ratio of Ni, Co, and Mn in NCM is 88:7:5).

[0080] Test Case

[0081] A battery is prepared using the lithium-ion ternary positive electrode materials of Examples 1-3 and the comparative example. The preparation method of the battery is as follows: (1) grinding and mixing the high-nickel ternary positive electrode material coated with LATP and the conductive carbon black to obtain a mixed powder, dissolving the binder PVDF using NMP to obtain a colloid, and then adding the mixed powder to the colloid and stirring to obtain a slurry with good fluidity, wherein the mass ratio of the high-nickel ternary positive electrode material coated with LATP: the conductive carbon black: the PVDF is 8:1:1; (2) coating the slurry on an aluminum foil to form a positive electrode sheet; (3) drying the positive electrode sheet to remove the solvent in the slurry, and then punching and cutting to obtain a circular sheet required for a button test; (4) assembling the positive electrode sheet, the separator, and the lithium metal negative electrode into a button battery.

[0082] The prepared battery was subjected to performance tests, and the test results are shown in Table 1.

[0083] Table 1 Battery performance test results

[0084]

[0085] From the results in Table 1, we can see that:

[0086] The LATP prepared in this embodiment not only increases the charge and discharge capacity of the material after coating the high nickel ternary positive electrode material, but also because the LATP surface coating increases the material ion conductivity, and lithium ions can migrate quickly through the coating during the charge and discharge process. In addition, the coating has better chemical stability to the electrolyte, and can better protect the internal material structure stability during the cycle, thereby improving the cycle retention rate.

[0087] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a lithium ion solid electrolyte, characterized in that: It includes the following steps: S1. dissolving the aqueous thickener in pure water to obtain a colloid, dividing the colloid into two parts and recording them as colloid A1 and colloid A2 respectively; S2. Adding lithium salt, aluminum salt and titanium salt to the colloid A1, and adding an organic chelating agent in a water bath; S3. neutralizing the alkaline substance A with purified phosphoric acid to form a phosphate solution and adding the phosphate solution to the colloid A2; S4. The colloid A1 is mixed with the colloid A2, and an alkaline substance B is added under stirring in a water bath to adjust the pH to obtain a mixed colloid; Then the temperature is raised and the stirring speed is increased to obtain a suspension; S5. Filter the suspension, wash and dry to obtain a LATP precursor, calcine and ball-mill the LATP precursor to obtain a lithium-ion solid electrolyte.

2. The method for preparing a lithium ion solid electrolyte according to claim 1, characterized in that: In step S1, the aqueous thickener is one of hydroxypropyl methylcellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, carboxymethyl cellulose, and sodium carboxymethyl cellulose; And / or, in the colloid, the mass percentage of the water-based thickener is 1%-2.5%, and the viscosity of the colloid is 2000-3000 mPa·s.

3. The method for preparing a lithium ion solid electrolyte according to claim 1, characterized in that: In step S2, the lithium salt is lithium nitrate or lithium chloride; And / or, in step S2, the aluminum salt is aluminum nitrate; And / or, in step S2, the titanium salt is one of potassium titanium oxalate, titanium oxalate, and titanyl sulfate; And / or, in step S2, the organic chelating agent is citric acid or oxalic acid; And / or, in step S2, the temperature of the water bath is 1-10°C; And / or, in step S2, according to the chemical formula of LATP Li 1+x Al x Ti 2-x (PO4)3 calculate the added amounts of the lithium salt, aluminum salt and titanium salt, wherein the concentration range of the Al element is 0.065-0.36 mol / l, 1.3≤x≤1.8; And / or, in step S2, the amount of the organic chelating agent is 0.5-2 times the total amount of the titanium aluminum metal ion substances.

4. The method for preparing a lithium ion solid electrolyte according to claim 1, characterized in that: In step S3, the alkaline substance A is ammonia water, sodium hydroxide or potassium hydroxide; And / or, in step S3, according to the chemical formula of LATP Li 1+x Al x Ti 2-x (PO4)3 calculates the amount of the phosphate solution added, and the concentration of the phosphate solution is 0.15-0.6 mol / l.

5. The method for preparing a lithium ion solid electrolyte according to claim 1, characterized in that: In step S4, the temperature of the water bath is 1-10°C; And / or, in step S4, the alkaline substance B is ammonia water, sodium hydroxide or potassium hydroxide; And / or, in step S4, the molar concentration of the alkaline substance B is 0.01-1 mol / l, and the pH of the mixed glue is 6-10; And / or, in step S4, the stirring speed in the water bath is lower than 60 rpm / min, and the reaction time is 2-8 h; And / or, in step S4, the heating is to raise the temperature of the mixed glue solution to 70-90° C., and the increasing the stirring speed is to increase the stirring speed to not less than 200 rpm / min; And / or, in step S4, the viscosity of the suspension is less than 500 mPa·s.

6. The method for preparing a lithium ion solid electrolyte according to claim 1, characterized in that: In step S5, the drying temperature is 110-180°C; And / or, in step S5, the calcination temperature is 700-1100°C.

7. A lithium ion solid electrolyte, characterized in that: The lithium ion solid electrolyte is prepared by the method for preparing the lithium ion solid electrolyte according to any one of claims 1 to 6.

8. A method for preparing a lithium-ion ternary positive electrode material, characterized in that: It includes the following steps: The lithium ion solid electrolyte as claimed in claim 7 is mixed with a ternary high-nickel material, and calcined to obtain a LATP-coated lithium ion ternary positive electrode material.

9. The method for preparing a lithium ion ternary cathode material according to claim 8, characterized in that: The mass ratio of the LATP powder material to the ternary high-nickel material is 0.2-1.5%; And / or, in the ternary high-nickel material, the Ni content among Ni, Co and Mn accounts for more than 80%; And / or, the calcination temperature is 550-650°C.

10. A lithium ion ternary positive electrode material, characterized in that: It is prepared by the preparation method of the lithium ion ternary positive electrode material as described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • High-safety lithium ion battery based on hydroxypropyl methyl cellulose built-in quasi-solid electrolyte

    CN114094169A

  • Solid electrolyte thin film, method of manufacturing same, and battery including same

    CN115995618A

  • Method for preparing lithium aluminum titanium phosphate solid electrolyte step by step and application

    CN117049497A

  • Apparatus of cosmetics shower for companion animal with antibiotics disinfection

    KR1020230010097A